Genomic characterization of Comamonas kerstersii isolated from diarrheal patients in Bangladesh - Noshin Ibnat Rib; Fariza Shams; Fahad Khan; Senzuti Sharmin; Sakib Abrar Hossain; Abdus Sadique; Jahidul Alam; Pronoy Debnath; Arman Hossain; Aura Rahman; Syeda Naushin Tabassum; Tahrima Saiha Huq; et al. (PLoS ONE, 2026)
This study marks the first identification and genomic characterization of Comamonas kerstersii isolates from diarrheal patients in Bangladesh. We carried out the whole genome sequencing of three C. kerstersii isolates to analyze genomic features using bioinformatics tools. We hypothesize that C. kerstersii can contribute to the diarrheal disease process through indirect mechanisms, potentially by interacting synergistically with other enteric pathogens such as Vibrio cholerae (both O1 and non-O1 serogroups). The presence of diverse virulence factors, including type IV pili, type VI secretion systems, chemotaxis proteins, and toxin genes such as zot and RTX, suggests a capacity for adhesion, motility, and immune evasion. Notably, genomic analyses indicate that C. kerstersii shares several offensive and defensive virulence factors with other pathogenic Comamonas spp, including mechanisms for biofilm formation, nutrient acquisition, and stress tolerance. These factors, combined with antimicrobial resistance genes identified genes – aph(6)-Id, aph(3”)-Ib, mph(E), mph(F), msr(E), sul2, and tet(A), may enhance survival and adaptability of C. kerstersii in the gut environment, potentially augmenting the pathogenicity of co-infecting diarrheal pathogens. These initial findings highlight the need for extensive genomic surveillance across diarrheal patients, along with further investigation into molecular interactions with co-pathogens that could reveal novel pathways influencing diarrheal disease outcomes.